2010
DOI: 10.1063/1.3456712
|View full text |Cite
|
Sign up to set email alerts
|

Sodium migration pathways in multicomponent silicate glasses: Car–Parrinello molecular dynamics simulations

Abstract: The mechanism of sodium migration in low-silica alkali-alkaline earth silicate glasses is investigated through Car-Parrinello molecular dynamics (MD) simulations. The transport of sodium to the glass surface and its subsequent release is critical for the use of these glasses in biomedical applications. The analysis of the MD trajectory, mainly through a combination of space and time correlation functions, reveals a complex mechanism, with some common features to the migration in mixed-alkali silicate glasses a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
74
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 75 publications
(83 citation statements)
references
References 51 publications
8
74
0
1
Order By: Relevance
“…We have shown that the initial Na + /H + exchange at the interface involves water dissociation at an Na + -NBO − pair, with release of the Na cation from the surface: because transport of further Na + ions from the bulk glass to the surface is thus essential to promote complete protonation of surface NBOs, additional CPMD simulations are currently addressing Na migration in these materials (Tilocca 2010b). Moreover, the effect of surface interactions on the water structure and connectivity has been investigated; the relatively low availability of favourable targets for HB interactions on the surface significantly affects water coordination in this region.…”
Section: Discussionmentioning
confidence: 99%
“…We have shown that the initial Na + /H + exchange at the interface involves water dissociation at an Na + -NBO − pair, with release of the Na cation from the surface: because transport of further Na + ions from the bulk glass to the surface is thus essential to promote complete protonation of surface NBOs, additional CPMD simulations are currently addressing Na migration in these materials (Tilocca 2010b). Moreover, the effect of surface interactions on the water structure and connectivity has been investigated; the relatively low availability of favourable targets for HB interactions on the surface significantly affects water coordination in this region.…”
Section: Discussionmentioning
confidence: 99%
“…Vibrational 11,20,21 and elastic 22 properties of the glass at ambient pressure have also been studied and successfully compared to experimental data. Using superomputers, large scale classical simulations have recently been performed 23 , as well as ab initio Molecular Dynamics simulations [24][25][26] . However, to our knowledge, no systematic study of the evolution of the system according to pressure has been performed so far.…”
Section: Introductionmentioning
confidence: 99%
“…However, significant changes to the coordination environment of the ion itself do occur during its migration from a site to another, when the ion often visits intermediate configurations which are significantly distorted with respect to the stable initial and final states [26,48]. For instance, Fig.…”
Section: Aimd Versus Classical MDmentioning
confidence: 97%
“…Ab-initio MD (AIMD) can usually target systems of few hundreds atoms and time scales of few tens of picoseconds [26][27][28][29][30][31]. In the case of glasses, this means that it is possible to perform an AIMD melt-and-quench simulation of a system around 100-200 atoms, using quenching rates around 20-100 K/ps [31][32][33][34].…”
Section: Aimd Versus Classical MDmentioning
confidence: 99%